PENGARUH SIKAP KERJA DAN KETERAMPILAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN CV. MERANTI MEDAN - Pitriyani Pitriyani; Abd. Halim (LPPM Universitas Labuhanbatu, 2020)
This study aims to determine how the influence of work attitudes and work skills on labor productivity at CV. Meranti Medan. Data collection in this study was carried out through a survey approach with quantitative descriptive research type by distributing questionnaires to 40 respondents, while the population used in this study were employees of CV Meranti Medan. The data analysis tool used in this study was SPSS (Statistical Product Software Solution). The results of this study indicate that partially (t test) work attitudes have a positive and significant effect on work productivity with a tcount of 6,027. Work skills have a positive and significant effect on work productivity with a tcount of 3.256. Simultaneously work attitudes and work skills together have a positive and significant effect on work productivity with an Fcount of 58,570. Through testing the coefficient of determination (R Square) of 0.89 or 89% which indicates that labor productivity is explained by Work Experience, Work Attitudes and Work Skills the remaining 11% is explained by other variables not included in this study.